Marxism, Atheism, Man - Repšys, Jonas (Problemos, 1968)
Summing up our atheistic literature and propaganda the author points out that it is not always effective enough. The matter is that the social role of religion is sometimes interpreted not from Marxist positions, but in a metaphysical and enlightened way. Applying Marxist methodology to the interpretation of historical processes the author underlines that atheism should reveal human problems comprised in religion and show its role in the life of society and of separate individuals; it should not be limited to pure negation.